ANALISIS EFISIENSI PENERIMAAN PENDAPATAN ASLI DAERAH (PAD) DI PROPINSI DI INDONESIA (APLIKASI MODEL DATA ENVELOPMENT ANALISYS) - Sri Kusreni (MediaTrend, 2010)
Indonesia is a big country with 32 provinces. Tax and retribution is used by every province to increase their income. Hence, tax and retribution is an important income source for regional government, as well as a part of public participation for regional development.The problems in regional development are the contribution of tax and retribution is not significant. As one of regional income (PAD) components, tax and retribution may be not efficient. In Product Domestic Regional Bruto (PDRB) efficient income concept is to optimalize value of money income, were is not only efficient in value but there must be effective. The aim of this research is to analysis output and input inefficiency in PAD for 30 provinces in Indonesia.Using Data Envelopment Analysis (DEA) with assumption Constant Return to Scale from total input and output side, the results shows that the conditions from 22 provinces in Indonesia only 8 provinces are not efficient.